Effectiveness of RemoteXs System in Teaching and Research Practices - Shakya, Pratichya; Nyaichyai, Lila (Curriculum Development Journal, 2022)
Tribhuvan University Central Library (TUCL) has implemented Remote Access Services through the RemoteXs system to impart efficient e-resources services for its users mainly after the Covid-19 pandemic. This study aims at investigating the effectiveness of that system in teaching and research practices at Tribhuvan University. This study is based on a quantitative approach. Post positivist ontology has been adopted as a research paradigm that identifies that all observations are imperfect and have errors and all theory is revisable. The survey questionnaire was used to collect data. The population comprised faculty, Ph.D. scholars, and M. Phil. students among which 105 users were taken as a sample size. The demographic data and statistical data were analyzed using Excel, 2007. Hypotheses were tested to find out their effectiveness on teaching and research practices. This study proved that the p-value (p = 1.96) suggested a significant contribution to the effectiveness of the RemoteXS system in teaching and research practices. It is observed that the system provided current academic and research products in an easy and accessible way to faculties and M.Phil as well as Ph.D. students. High Likert scores on variables; increased productivity after use, perceived usefulness, perceived ease of use, relevancy of content, advanced search system, saving the time of users, and document downloading facilities also indicated the effective use of it by faculties and research students. At last, the issue of the unavailability of Nepal digital resources has been emphasized which would have been used rigorously for the conduction of research in the context of Nepal.